2004
DOI: 10.1159/000081368
|View full text |Cite
|
Sign up to set email alerts
|

A Third Case of Cardiac Neoplasm in a Fetus with Beckwith-Wiedemann Syndrome: Epicardial Angiofibroma

Abstract: Objective: A personal observation of a 20-week-old fetus with Beckwith-Wiedemann syndrome (BWS) presenting epicardial angiofibroma prompted us to evaluate cardiac neoplasms in this genetic condition. Method: We performed an autopsy and a histological evaluation of the fetus, and searched the literature for cardiac anomalies in BWS. Results: Although cardiac tumors are exceptional and although BWS is rare, we found two other cardiac neoplasms in infants with BWS, whereas no more than one was expected. Conclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Recently, Weksberg et al [2001Weksberg et al [ , 2003 demonstrated that BWS is associated with alterations in two distinct imprinting domains at 11p15: a telomeric domain containing H19 and IGF2 and a centromeric domain including KCNQ1, KCNQ1OT1, and CDKN1C. Reddy et al, 1972;Raine et al, 1979;Gaillard et al, 1981;Bockrath et al, 1982;SolsonaNarbon et al, 1992;Hayward et al, 1988;Williams et al, 1990;Walton et al, 1991;Crankson and Ahmed, 1991;Chan et al, 1994;Craver and Heinrich, 1995;Akata et al, 1997;Herman et al, 1997;Jonas and Kimonis, 2001;Fukuzawa et al, 2001;Cohen et al, 2002;Anoop and Anjay, 2004;Satge et al, 2005. [Weksberg et al, 2001].…”
Section: Beckwith-wiedemann Syndromementioning
confidence: 99%
“…Recently, Weksberg et al [2001Weksberg et al [ , 2003 demonstrated that BWS is associated with alterations in two distinct imprinting domains at 11p15: a telomeric domain containing H19 and IGF2 and a centromeric domain including KCNQ1, KCNQ1OT1, and CDKN1C. Reddy et al, 1972;Raine et al, 1979;Gaillard et al, 1981;Bockrath et al, 1982;SolsonaNarbon et al, 1992;Hayward et al, 1988;Williams et al, 1990;Walton et al, 1991;Crankson and Ahmed, 1991;Chan et al, 1994;Craver and Heinrich, 1995;Akata et al, 1997;Herman et al, 1997;Jonas and Kimonis, 2001;Fukuzawa et al, 2001;Cohen et al, 2002;Anoop and Anjay, 2004;Satge et al, 2005. [Weksberg et al, 2001].…”
Section: Beckwith-wiedemann Syndromementioning
confidence: 99%
“… MYH8? 608837 Veugelers et al ( 2004 ) Stratakis et al ( 2004 ) Beckwith-Wiedemann (BWS) Overgrowth, macroglossia, omphalocele, hemihypertrophy Rhabdomyoma or angiofibroma or hamartoma in the setting of macrosomia Imprinting disorder 11p15 region (loci IC1 and IC2; CDKN1C , KCNQ10T1 , KCNQ1 , IGF2 , H19 genes) 130650 Longardt et al ( 2014 ) Reddy et al ( 1972 ) Satgé et al ( 2005 ) Neurofibromatosis type 1 Characteristic skin changes, neurofibromas, optic gliomas Neurofibroma Autosomal dominant 17q11.2micro-/deletions involving NF1 613675 Nguyen et al ( 2013 ) Birt-Hogg-Dube (BHD) Lung cysts, colonic polyps, renal tumors Rhabdomyoma Autosomal dominant FLCN 135150 Toro et al ( 2008 ) Hereditary paraganglioma/pheochromocytoma syndromes (including Carney-Stratakis syndrome and Carney triad) Paragangliomas, gastric stromal sarcomas or leiomyosarcomas, pulmonary chondromas Paraganglioma Autosomal dominant? SDHB , SDHC , SDHD 606864, 604287 Miraldi et al ( 2007 ) Cowden syndrome (CS) Macrocephaly, hamartomas, ovarian cysts, cancer Lipoma Autosomal dominant PTEN 158350 Ceresa et al ( 2010 ) Familial myxoma Atrial myxomas Myxoma Autosomal dominant PRKAR1A 255960 Singh and Lansing ( 1996 ) …”
Section: Discussionmentioning
confidence: 99%
“…However, according to our literature research, CRs have not yet been described in the context of BWS. We found only three cases of intracardiac tumors associated with BWS in the literature: (1) a stillborn child at 22 3/7 weeks' gestation with epicardial angiofibromas; (2) a 2‐year‐old boy with fibromatous hamartoma of the upper part of the interventricular septum, who died because of a nephroblastoma; and (3) an 8‐month‐old boy with hamartomas, also called histocytoid cardiomyopathy …”
Section: Discussionmentioning
confidence: 99%